(untitled) (Research, Society and Development, 2020)
This paper consists of an experience report of the professional experience in teaching the contente of the Geography to students of the Integrated Technical Teaching of the Federal Institute od Education, Science and Technology of Minas Gerais – campus Betim, in the face of the emergency scenario of adopting a teaching emergency remote control, mostly via Digital Information and Communication Technologies (DICTs). Concepts and theories related to education, teaching and the teaching-learning relationship are presented that support discussions related to the diferente possibilities of teaching methods and learnig styles. This foundation supports the examples presented, which were distributed via the Virtual Learning Environment (VLE). Thus, the purpose of this repor tis to present and discuss the strategies adopted in classes and evaluative activities. It is observed that, given the exceptional character of the year 2020, pandemic and remote education, it was possible to maintain importante relationships, such as teacher-student and school-student. In addition, it is possible to affirm that the variation in the teaching methods provided engagement, interest and involvement of the students, which was evidenced by the participation in the synchronous classes and by the comments after the fulfillment of activities. In this way, what would be an emergency possibility for the current teaching contexto has become an importante tool when resuming face-to-face activities.